Exuberant Choroidal Melanoma in COVID-19 Era - Marta, Ana (2022)
A 61-year-old man presented with a superior visu- al field defect on his right eye (RE), for 3 months, but he delayed coming to the emergency department for fear of coronavirus. His best-corrected visual acuity of the RE was 1.25/10 and biomicroscopy generated unremarkable findings. A large, dome-shaped, pigmented, and peripheral lesion with an adjacent exsudative retinal detachment was seen on ophthalmoscopy and documented by an ultra-wide field pseudocolor photograph captured using Optos (Fig. 1). B-scan ultrasonography confirms a low-moderate internally reflective dome-shaped choroidal lesion, sized 13x12 mm, with adjacent retinal detachment. The optical coherence tomography of the macula showed subretinal fluid reaching the fovea. Patients are avoiding medical care due to fear of coronavirus.1 Regarding choroidal melanoma, patients will present with more advanced disease with lost opportunities for conserving vision and the eye.2 We want to alert to this new reality that we have been facing and the need to provide health literacy, avoiding unnecessary costs for patients, and conserve healthcare resources.